What Is the Importance of Second‐Trimester "Soft Markers" for Trisomy 21 After an 11‐ to 14‐Week Aneuploidy Screening Scan?. (1st October 2014) - Bromley, Bryann; Shipp, Thomas D.; Lyons, Jennifer; Groszmann, Yvette; Navathe, Reshama S.; Benacerraf, Beryl R.
Abstract : Objectives: The purpose of this study was to evaluate the importance of second‐trimester "soft markers" for trisomy 21 after an 11‐ to 14‐week aneuploidy screening scan. Methods: We conducted a retrospective cohort study of consecutive patients referred for measurement of the nuchal translucency (NT) as part of a screening protocol for aneuploidy. Patients who returned for an anatomic survey between 16 and 20 weeks' gestation were evaluated. The sonographic markers and anomalies associated with the detection of trisomy 21 in the second trimester were analyzed. Results: There were 42 fetuses (0.4%) with trisomy 21 identified in the study cohort of 9692 patients. Trisomy 21 was suspected at the NT scan in 28 fetuses (67%) and at the second‐trimester anatomic survey in 14 (33%). In fetuses first suspected of having trisomy 21 in the second trimester, 9 of 14 had normal anatomic survey results, and 5 of 14 had congenital malformations. All 14 fetuses had soft markers for aneuploidy. A thickened nuchal fold was identified in 5 of 9 fetuses with trisomy 21 and normal anatomic survey results, all of whom had an NT of less than 3.0 mm at the initial screening scan. Conclusions: Second‐trimester soft markers, especially a thickened nuchal fold, remain important observations in the detection of trisomy 21 by sonography among fetuses who have had first‐trimester sonographic screening for aneuploidy.